Selected structural parameters and thermal and mechanical properties of blends of poly(ethylene terephthalate), isotactic polypropylene grafted with ricinyl-2-oxazoline maleate and polycarbonate (PET/i-PP-g-MRO/PC) - Jeziórska, R. (Polimery, 2022)
The effect of reactive polypropylene functionalized with oxazoline groups (i-PP-g-MRO) on phase structure and mechanical properties of PET/i-PP-g-MRO/PC obtained in result of combining processes of reactive extrusion and fast electron irradiation was investigated. The blends are characterized by heterogeneous structure, which in result of chemical reactions occurring during extrusion, stabilizes at the microphase level, with interpenetrating phases resulting, having advantageous effecton mechanical properties. Investigation result point to compatibilizing effect of the oxazoline derivative.